Socialization of Independent Waste and Household Waste Management for PKK Women in Tanjung Barat Subdistrict - Anita Nurfida; Nur Arifiya; Tri Novita Sari (Universitas PGRI Sumatera Barat, 2024)
The waste problem in the city of Jakarta is a national issue that should not be taken lightly. This is because Jakarta is one of the largest cities in Indonesia, so it is a benchmark and is looked up to by all countries in the world. The volume of waste in Jakarta which continues to increase every year is a chore not only for the government but also for the people who contribute to producing it. If this rubbish is left unattended, it will cause environmental problems such as flooding, environmental pollution and even health problems. Organic waste occupies the largest percentage of waste contributors in Jakarta, namely in 2020 - 2021 the volume of organic waste reached 54% of the total existing waste, while in 2022 it will reach 50% of the total existing waste. Apart from organic waste, there are other types of waste such as inorganic waste and B3 waste. So far, residents of RT 11/RW 02 Tanjung Barat Subdistrict, Jagakarsa District still have minimal knowledge about rubbish and waste generated from household activities and still lack concern for protecting the environment. The aim of this service is to provide material to increase the knowledge of PKK RT11/RW 02 women in Tanjung Barat sub-district about various types of waste and household waste produced and how to manage it independently in the household. From the results of this community service activity, it can be concluded that the socialization about waste and waste management is very beneficial for the women of PKK RT11/RW 02, Tanjung Barat sub-district because it can be a solution in reducing the existing problem of waste and household waste so that the environment is clean and beautiful.